“I then for the first time felt fearful she might not rally…”: a discourse analysis of the nineteenth century case reports in ophthalmology - Zabielska, Magdalena (Scripta Neophilologica Posnaniensia, 2019)
The present paper constitutes a qualitative discursive investigation of the nineteenth century case reports from ophthalmology derived from a specialist American medical journal, and focuses on citation as well as on authorial and patient’s presence. Regarding the first aspect, the present study generally confirms the results of the previous research, i.e. significant subjectivity, directness and informal character of the texts at hand. However, it also provides another insight into the scholarly communication in the nineteenth century, focusing on how patients are positioned therein, which has not received significant attention in the literature of the subject. Additionally, the paper offers an overview of the studies on specific aspects of scientific prose of the nineteenth century, including the medical context, as well as attempts to show the relation between the texts analysed and the context of their production and functioning, following the tradition of Genre Rhetorical Studies.